2017
DOI: 10.2147/ott.s134290
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic value of 3-D printing template-assisted <sup>125</sup>I-seed&nbsp;implantation in the treatment of malignant liver tumors

Abstract: ObjectiveTo explore the therapeutic value of 3-D printing template-assisted 125I-seed implantation in the treatment of malignant liver tumors.Materials and methodsFifteen liver cancer patients with 47 total lesions were treated with 3-D printing template-assisted radioactive seed implantation (group A), and 25 liver-tumor patients with 66 total lesions were treated with 125I-seed implantation without a template auxiliary (group B). Operation time, in-hospital time, operation complications, dose distribution, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…According to preoperative CT data, a high-precision 3D model can be printed and used to make the morphology of an implantation material conform to individual anatomy[20,23-26]. This technology has also been preliminarily applied in template preparations for neck, pulmonary, abdominal, and pelvic tumor iodine-125 seed implantation, and the postoperative dosimetry was consistent with treatment planning[12,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…According to preoperative CT data, a high-precision 3D model can be printed and used to make the morphology of an implantation material conform to individual anatomy[20,23-26]. This technology has also been preliminarily applied in template preparations for neck, pulmonary, abdominal, and pelvic tumor iodine-125 seed implantation, and the postoperative dosimetry was consistent with treatment planning[12,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…In total, 145 candidate publications were retrieved. Ultimately, 16 studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] which fullfilled the eligibility criteria were included in the final analysis (see Fig. 1 for further details).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…All of the researches originated from China., including 16 non-RCTs. Eight original articles [12][13][14][15][16][17][18][19] with 280 patients compared the dose distribution differences between 3D print template-assisted implantation and traditional free-hand implantation. Among them, 128 patients received 3D print template-assisted RIS implantation and 152 without template.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Han et al . [ 18 ] compared the differences of dosimetric parameters between RIS implantation assisted with 3D-PNCT and without 3D-PNCT in treating liver tumors. The results showed that D 100 , V 100 , and V 150 values were significantly different between the two groups.…”
Section: Discussionmentioning
confidence: 99%